Psychological pressure and compounded errors during elite-level tennis - Harris, D. J.; Vine, S. J.; Eysenck, M. W.; Wilson, M. R. (Psychology of Sport and Exercise, 2021)
Objectives: In the context of Grand Slam tennis, we sought to examine how situational pressure and prior errors can disrupt subsequent performance in elite performers. Methods: A retrospective analysis of more than 650,000 points across 12 Grand Slam tennis tournaments from 2016 to 2019 was conducted to identify pressurised in-game moments and unforced errors. A scoring system was used to index situational pressure based on the current match situation (e.g., break points, stage of the match) on a point-by-point basis. The occurrence of performance errors was identified based on double faults and unforced errors, as instances of controllable mistakes. Results: A mixed effects logistic regression model revealed that an increase in the pressure index (a 1-5 score) significantly increased the probability of a performance error (ps < .001), as did an error on the preceding point (OR = 1.2, 95%CI [1.17, 1.23], p < .001). A multiplicative effect of pressure and prior errors also emerged, as the negative impact of prior errors on performance was greater when situational pressure was already high, in line with the predictions of Attentional Control Theory: Sport (ACTS). Analyses of the distribution of winners and unforced errors across individual players revealed that winning players were as susceptible to pressure and prior errors as losing players. Conclusions: These findings extend our understanding of how ongoing feedback from prior mistakes may further exacerbate the effects of pressure on performance.